Epidural tramadol improves the quality of pain relief during labor - Shrestha, I N; Deo, G P; Shrestha, S K; Neupane, S; Regmi, B S (Journal of Chitwan Medical College, 2017)
To study the analgesic efficacy and side effects of Tramadol for painless labor in combination with Bupivacaine. Randomized, controlled, double blind, open prospective study conducted at Department of Obstetrics and Gynaecology, Chitwan Medical College from July 1st 2015 to June 30th 2016. 100 patients of ASA Grade I and II, aged between 20-35 years willing for epidural analgesia for labor pain were included in the study. They were divided into two groups: Group A- Control group and Group B- Study group. Subjects of Group A received 10 ml of 0.25% Bupivacaine and that of Group B received 10ml of 0.25% Bupivacaine with 1mg/kg body weight of tramadol. Analgesic efficacy was assessed by Visual Analogue Scale (VAS) and other vital parameters (Blood Pressure, Heart Rate and Respiratory Rate) before the administration of the drug and at different time intervals of 0, 5 min, 10 min, 15 min, 30 min, 45 min, 60 min and every hourly up to maximum of 5 hrs. Neonatal out comes were assessed by the use of APGAR scores and the side effects of the drugs in two groups were also evaluated. Total number of patients was 100, of ASA Grade I and II, aged between 20-35 years. The mean age of patients in Group A was 23.54 ± 3.74 years and 24.22 ± 3.64 years in Group B. Mode of delivery was spontaneous vaginal in 42 patients (84%) in group A and 45 patients (90%) in group B. Instrumental vaginal delivery was done in 1 patient (2%) of group A and none of group B. Cesarean section was done in 7 patients (14%) of group A and 5 patients (10%) of group B. There was no significant difference in heart rate, blood pressure and respiratory rate at various time intervals. Pain score of Group B was significantly less at 60th min and had lower values than Group A at various time intervals. Time for first top up was significantly delayed and the total dose of bupivacaine was significantly lower in Group B patients but the incidence of nausea and vomiting was significantly high among Group B patients. At one minute majority of the babies of group A had mean APGAR score 6.98 ± 0.55 versus 7.18 ± 0.60 in group B. At 5 minute, Group A had mean score of 8.02 ± 0.47 versus 8.22 ± 0.58 in Group B. There were no significant differences in 2 groups. In both the groups there was no significant effect on duration of second stage of labor and it wasn’t prolonged in any of the patients. Epidural anesthesia with bupivacaine and tramadol provided better pain relief and reduced the total dose of bupivacaine in majority of the patients with no adverse effects on mother and fetus. As tramadol is cheap, safe and effective, it can be considered as a better option to improve quality of pain relief during labor.